2015
DOI: 10.1371/journal.pone.0132147
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in Soil Physical and Chemical Properties in Long Term Improved Natural and Traditional Agroforestry Management Systems of Cacao Genotypes in Peruvian Amazon

Abstract: Growing cacao (Theobroma cacao L.) in an agroforestry system generates a productive use of the land, preserves the best conditions for physical, chemical and biological properties of tropical soils, and plays an important role in improving cacao production and fertility of degraded tropical soils. The aim of this study was to evaluate the impact of two long term agroforestry systems of cacao management on soil physical and chemical properties in an area originally inhabited by 30 years old native secondary for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 61 publications
(85 reference statements)
3
32
1
8
Order By: Relevance
“…The porosity also varies from 46.30 % (at settlement area) to 60.80 % (at the rice field area). This finding supports the earlier work by [11] who reported inverse relationship between bulk density and porosity of the soil.…”
Section: Soil Porosity and Permeabilitysupporting
confidence: 93%
“…The porosity also varies from 46.30 % (at settlement area) to 60.80 % (at the rice field area). This finding supports the earlier work by [11] who reported inverse relationship between bulk density and porosity of the soil.…”
Section: Soil Porosity and Permeabilitysupporting
confidence: 93%
“…Some high and low input technologies in long term trials have been tested in the humid acid tropical soil of Yurimaguas, Peru and one of the main options was the agroforestry systems (Palm, 1995;Alegre, 2015). The introduction of perennial cropping systems with coffee or cacao managed with cover crops also offers an alternative to recover degraded land in the Amazon (Puertas et al, 2008;Arévalo-Gardini et al, 2016). The potential of trees and cover crops to contribute to the maintenance and rehabilitation of the soil's physical characteristics such as better bulk density, mechanical resistance and soil aggregation has been well established, including an improvement on productivity (Alegre and Rao, 1996;Rao et al, 1998;Alegre et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…(Guan et al, 2018;Gao et al, 2013). Recently, many researchers have attached great importance to understanding the impacts (Arevalo-Gardini et al, 2015;Pang et al, 2011). Some studies have shown that harvesting not only destroys the physical properties of the soil, but also affects the chemical properties, especially the soil water holding capacity and soil porosity.…”
Section: Introductionmentioning
confidence: 99%